2023
DOI: 10.1186/s12913-023-09038-x
|View full text |Cite
|
Sign up to set email alerts
|

How to become an excellent pediatric resident: a qualitative comparative study from China

Abstract: Background Competency-oriented medical education has become a global trend. However, most current studies focus on the independent effects of various competencies and lack an examination of the combined effects. Therefore, the purpose of this study was to explore the competency configurations of excellent pediatric residents and general pediatric residents and to provide a scientific reference for the talent training and career development of pediatric residents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Scholarly activity has been reported to have a positive impact on residents' clinical performance, patient outcomes, residents' examination scores, and career development 5,6,8,25–27 . Our study similarly indicated that publication was associated with certification test success.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Scholarly activity has been reported to have a positive impact on residents' clinical performance, patient outcomes, residents' examination scores, and career development 5,6,8,25–27 . Our study similarly indicated that publication was associated with certification test success.…”
Section: Discussionsupporting
confidence: 70%
“…Scholarly activity has been reported to have a positive impact on residents' clinical performance, patient outcomes, residents' examination scores, and career development. 5,6,8,[25][26][27] Our study similarly indicated that publication was associated with certification test success. Not limited to association with examinations, scholarship is included among the key competencies in postgraduate training programs.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations